Sudirman: Muhammadiyah dan Mobilitas Sosial Pribumi - Sholawati Sholawati; Mahli Zainuddin Tago (JUSPI (Jurnal Sejarah Peradaban Islam), 2022)
The research was intended to describe the character general Sudirman as a person educated in Muhammadiyah, and how Muhammadiyah as an Islamic organization became a bridge in General Sudirman's social mobility. From a farmer's son to a general during the years of the end of the colonization and the beginning of Indonesia’s freedom, where social stratification systems were reckoned. It uses historical research methods, using the three stages of heuristic, historical criticism, and presentation or narration. Studies have shown that Sudirman is the most influential figure in defending Indonesia's freedom. Sudirman became one of only three Indonesian soldiers to earn the honorary title of a great general. His career began with his activity in the Muhammadiyah organization as Hizbul Wathan and the young Muhammadiyah. Character shaped during membership and leadership in the organization led Sudirman into a respected and trusted figure to become a war leader of the Indonesian’s army.